Factors that Influence Green Purchase Behavior by Green Purchase Intention on Green Apparel - Lim, Irine; Lady, Lady (International Journal of Indonesian Business Review, 2023)
This research is aims to confirmation of the influence of TPB (Theory Planned Behavior), willingness to pay and environmental consciousness on green purchase behavior by green purchase intention on green apparel. Respondents are received 343 that contains Y and Z generations from Batam by filled quetionnaires online. Data are analysed by PLS system. Findings of research are attitude has positive significant impact on intention but insignificant on behavior. Subjective norms and perceived behavioral are insignificantly on behavior and intention. Willingness to pay has positive significant impact on behavior but insignificant on intention. Environmental has positive significant impact on intention and ndegative significant on behavior. Green purchase intention has positive significant on behavior and worked as intervening to mediate others variables.